Schistosomicidal effects of histone acetyltransferase inhibitors against Schistosoma japonicum juveniles and adult worms in vitro. - Jing Xu; Jing-Yi Wang; Ping Huang; Zi-Hao Liu; Yu-Xin Wang; Run-Ze Zhang; Hui-Min Ma; Bi-Yue Zhou; Xiao-Yan Ni; Chun-Rong Xiong; Chao-Ming Xia (Public Library of Science (PLoS), 2024)
Background Schistosomiasis is a relatively neglected parasitic disease that afflicts more than 250 million people worldwide, for which the control strategy relies mainly on mass treatment with the only available drug, praziquantel (PZQ). This approach is not sustainable and is a priority for developing novel drug candidates for the treatment and control of schistosomiasis. Methodologys/principal findings In our previous study, we found that DW-3-15, a kind of PZQ derivative, could significantly downregulate the expression of the histone acetyltransferase of Schistosoma japonicum (SjHAT). In this study, several commercially available HAT inhibitors, A485, C646 and curcumin were screened in vitro to verify their antischistosomal activities against S. japonicum juveniles and adults. Parasitological studies and scanning electron microscopy were used to study the primary action characteristics of HAT inhibitors in vitro. Quantitative real-time PCR was employed to detect the mRNA level of SjHAT after treatment with different HAT inhibitors. Our results demonstrated that curcumin was the most effective inhibitor against both juveniles and adults of S. japonicum, and its schistosomicidal effects were time- and dose dependent. However, A485 and C646 had limited antischistosomal activity. Scanning electron microscopy demonstrated that in comparison with DW-3-15, curcumin caused similar tegumental changes in male adult worms. Furthermore, both curcumin and DW-3-15 significantly decreased the SjHAT mRNA level, and curcumin dose-dependently reduced the SjHAT expression level in female, male and juvenile worms. Conclusions Among the three commercially available HATs, curcumin was the most potent against schistosomes. Both curcumin and our patent compound DW-3-15 markedly downregulated the expression of SjHAT, indicating that SjHAT may be a potential therapeutic target for developing novel antischistosomal drug candidates.